Identification of Acid-Base Misconceptions and Efforts to Correct them with Problem-Based Cognitive Conflict Strategies - Gaudensiana Seko Taboy; Subandi Subandi; Hayuni Retno Widarti (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: The aims of this study were to identify the types of misconceptions; test the effectiveness of cognitive conflict strategies based on problem-solving in reducing misconceptions; measuring the retention of students' conceptual understanding. Misconceptions were identified using tests with modified Certainty of Response Index techniques and interviews. The effectiveness of cognitive conflict strategy based on problem-solving was determined based on the reduction of misconceptions and paired sample t-test, while the retention of students' understanding was determined three weeks after treatment by comparing the results of the posttest and postponement test. The results showed that there were 38 types of misconceptions; cognitive conflict strategies based on problem-solving proved to be effective in reducing misconceptions; three weeks after treatment, retention of students' concept understanding was very good.Abstrak: Penelitian bertujuan untuk mengidentifikasi jenis miskonsepsi; menguji efektivitas startegi konflik kognitif berbasis pemecahan masalah dalam mengurangi miskonsepsi; mengukur retensi pemahaman konsep siswa. Miskonsepsi diidentifikasi menggunakan tes dengan teknik Certainty of Response Index termodifikasi dan wawancara. Efektifitas strategi konflik kognitif berbasis pemecahan masalah ditentukan berdasarkan pengurangan miskonsepsi dan uji-t sampel berpasangan, sedangkan retensi pemahaman siswa ditentukan dengan membandingkan hasil postes dan tes tunda, tiga minggu setelah perlakuan. Hasil penelitian menunjukkan terdapat 38 jenis miskonsepsi; strategi konflik kognitif berbasis pemecahan masalah efektif dalam mengurangi miskonsepsi; tiga minggu setelah perlakuan retensi pemahaman konsep siswa termasuk kriteria sangat baik.